Osteoblast-Derived Vesicle Protein Content Is Temporally Regulated During Osteogenesis: Implications for Regenerative Therapies - Davies, Owen G.; Cox, Sophie C.; Azoidis, Ioannis; McGuinness, Adam J. A.; Cooke, Megan; Heaney, Liam M.; Davis, Edward T.; Jones, Simon W.; Grover, Liam M. (Frontiers in Bioengineering and Biotechnology, 2019)
Osteoblast-derived extracellular vesicles (EV) are a collection of secreted (sEVs) and matrix-bound nanoparticles that function as foci for mineral nucleation and accumulation. Due to the fact sEVs can be isolated directly from the culture medium of mineralising osteoblasts, there is growing interest their application regenerative medicine. However, at present therapeutic advancements are hindered by a lack of understanding of their precise temporal contribution to matrix mineralisation. This study advances current knowledge by temporally aligning sEV profile and protein content with mineralisation status. sEVs were isolated from mineralising primary osteoblasts over a period of 1, 2 and 3 weeks. Bimodal particle distributions were observed (weeks 1 and 3: 44 nm and 164 nm; week 2: 59 nm and 220 nm), indicating a heterogeneous population with dimensions characteristic of exosome- (44 and 59 nm) and microvesicle-like (164 and 220 nm) particles. Proteomic characterisation by liquid chromatography tandem-mass spectrometry (LC-MS/MS) revealed a declining correlation in EV-localised proteins as mineralisation advanced, with Pearson correlation-coefficients of 0.79 (week 1 vs. 2), 0.6 (2 vs. 3) and 0.46 (1 vs. 3) respectively. Principal component analysis (PCA) further highlighted a time-dependent divergence in protein content as mineralisation advanced. The most significant variations were observed at week 3, with a significant (p < 0.05) decline in particle concentration, visual evidence of EV rupture and enhanced mineralisation. A total of 116 vesicle-localised proteins were significantly upregulated at week 3 (56% non-specifically, 19% relative to week 1, 25% relative to week 2). Gene ontology enrichment analysis of these proteins highlighted overrepresentation of genes associated with matrix organisation. Of note, increased presence of phospholipid-binding and calcium channelling annexin proteins (A2, A5 and A6) indicative of progressive variations in the nucleational capacity of vesicles, as well as interaction with the surrounding ECM. We demonstrate sEV-mediated mineralisation is dynamic process with variations in vesicle morphology and protein content having a potential influence on developmental changes matrix organisation. These findings have implications for the selection and application of EVs for regenerative applications.